KONFLIK KEHARUSAN AKUNTABILITAS DAN KINERJA KERJA NGO DI INDONESIA - M. Yudhika Elrifi (Akademi Akuntansi YKPN Yogyakarta, 2014)
This research investigated the impact of konflik keharusan akuntabilitasin public setor organization, especially for Non Govermental Organization (NGO). Its provided empirical evidence on the impact factors determined the konflik keharusan akuntabilitasof work performance NGOs accountability actor in Indonesia. The objectives of research is to identify different types of accountability requirements with quantitative data and to determine that the competing pressures of accountability affect NGO’s perceived work performance. The results showed that work performance NGO’s accountability actor in Indonesia partly influenced by a negative perceived work context that is workload and job tension. Keywords: competing accountability requirement, competing accountability, NGO, work performance